Chemopreventive approach of Indian spice “Curcumin” in the treatment of breast cancer - Deb, Anuska; Mishra, Manshi; Kumar, Bimlesh; Kumar Pandey, Narendra; Singh, Saurabh; Singh Baghel, Dileep; Mazumder, Rupa; Ji Porwal, Om (Trends in Immunotherapy, 2024)
One of the primary concerns for women in good health is breast cancer. The most typical hazardous growth is this one. It spreads easily, and the clinical conditions are terrible. Bosom illness is the second‐most common type of malignant tumor that regularly causes women to pass away in the U.S. bosom malignant growth is the most well‐known disease among women worldwide, with 2.1 million cases reported in 2018 and more than 620,000 fatalities per year. Natural components are viewed as promising alternatives for the development of novel anti‐tumor drugs. Curcumin, also termed diferuloylmethane, is a yellow pigment made by the turmeric plant, Curcuma longa Linn. It is the curcuminoid and polyphenol present in the plant’s root that is most abundant. The antioxidant and anti‐inflammatory qualities of curcumin have been demonstrated, and it is frequently utilized in traditional medicine and cuisine. Due to its sophisticated pharmacological capabilities of chemoprevention and anticancer effects, curcumin, the main component of turmeric, has been linked to the treatment of breast cancer. The morbidity or mortality of the disease have not been significantly decreased by current breast cancer treatment options such as surgery, radiation, adjuvant chemotherapy, or hormone therapy. The expansion, estrogen receptor (trauma center), and human epidermal development factor receptor 2 (HER2) pathways are all involved in the activity of curcumin in illness. In breast cancer cells, curcumin is also known to regulate microRNA, cell stage-related characteristics, and apoptosis. This study reviews recent research on the atomic targets and anticancer effects of curcumin in breast cancer.